Low eicosapentaenoic acid and gamma-linolenic acid levels in breast adipose tissue are associated with inflammatory breast cancer. (June 2019) - Chas, Marie; Goupille, Caroline; Arbion, Flavie; Bougnoux, Philippe; Pinault, Michelle; Jourdan, Marie Lise; Chevalier, Stephan; Ouldamer, Lobna
Abstract: Objective: Since it is thought that breast adipose tissue could influence breast cancer clinical presentation, we wanted to characterize specifically the relationship between breast adipose tissue fatty acid profile and Inflammatory Breast cancer (IBC). Methods: Two hundred thirty-four women presenting with breast cancer were managed in our centre between January 2009 and December 2011. Breast adipose tissue specimens were collected during breast surgery. We established the biochemical profile of adipose tissue fatty acids (FA) by gas chromatography and assessed whether there were differences in function of the presence of breast inflammation or not. Results: We found that IBC was associated with decreased levels in breast adipose tissue of eicosapentaenoic acid (EPA), one of the two main polyunsaturated n-3 fatty acids (n-3 PUFA) of marine origin, but also with decreased levels of Gamma Linolenic acid (GLA). Inversely, an increase in palmitic acid levels was associated with IBC. Conclusion: These differences in lipid content may contribute to the occurrence of breast cancer inflammation. Highlights: We studied the relationship between breast adipose tissue fatty acid profile and Inflammatory Breast cancer (IBC). We established the biochemical profile of adipose tissue fatty acids (FA) by gas chromatography. IBC was associated with decreased levels in breast adipose tissue of eicosapentaenoic acid. IBC was associated with decreased levels in breast adipose tissue of Gamma Linolenic acid (GLA). Inversely, an increase in palmitic acid levels was associated with IBC.